Extension Of Pacmad Model For Usability Evaluation Metrics Using Goal Question Metrics (GQM) Approach - Norasikin Fabil; Ashraf Saleh; Roesnita Binti Isamil (JATIT & LLS, 2024)
Journal of Theoretical and Applied Information Technology 10th September 2015. Vol.79. No.1